2019
DOI: 10.3390/s19071559
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Multiple Fano Resonances for On-Chip Sensors in a Plasmonic System

Abstract: This paper proposed a plasmonic resonator system, consisting of a metal-insulator-metal structure and two stubs, and a Fano resonance arose in its transmittance, which resulted from the coupling between the two stubs. On the basis of the proposed structure, a circle and a ring cavity are separately added above the stubs to create different coupled plasmonic structures, providing triple and quadruple Fano resonances, respectively. Additionally, by adjusting the geometric parameters of the system, multiple Fano … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 43 publications
(72 reference statements)
0
22
0
Order By: Relevance
“…From the table we can draw the conclusion that our structure has relatively good sensitivity and it is superior to other structures in both the maximal FOM and the number of Fano or EIT-like resonances [6], [18]- [21], [40]- [45], [53], [55], [64]- [67]. Besides, the slow light effects of our system outperform other researches in the reference [20], [54]- [57], which shows great promises for highly integrated slow light applications. And it is worth mentioning that the extinction ratio of the proposed system is higher than that of most other proposed structures in the reference [7], [59], [60].…”
Section: Switching Applications Of the Systemmentioning
confidence: 80%
See 2 more Smart Citations
“…From the table we can draw the conclusion that our structure has relatively good sensitivity and it is superior to other structures in both the maximal FOM and the number of Fano or EIT-like resonances [6], [18]- [21], [40]- [45], [53], [55], [64]- [67]. Besides, the slow light effects of our system outperform other researches in the reference [20], [54]- [57], which shows great promises for highly integrated slow light applications. And it is worth mentioning that the extinction ratio of the proposed system is higher than that of most other proposed structures in the reference [7], [59], [60].…”
Section: Switching Applications Of the Systemmentioning
confidence: 80%
“…The FOM is another crucial and more illustrative parameter to evaluate the sensing performance of the system, expressed as FOM = T /T n [20], where T is the transmittance of the system and T / n denotes the transmittance variation at the constant wavelength induced by the alteration of n. As can be seen from figure 7(c), the FOMs are calculated for the refractive indexes 1.01, 1.02, and 1.03 as FOM = (T n=1.01/1.02/1.03 − T n=1 )/(T n=1 n), among which the maximum can reach 2685 at 949 nm, which is larger than that in the previous report about refractive index sensors [40], [50], [53]. Similarly, we further explore the sensing potential of the derived system in section III.B, which is displayed in figure 8(a), (b) and (c).…”
Section: Potential Applications Of the Proposed Multiple Fano Andmentioning
confidence: 99%
See 1 more Smart Citation
“…It can obtain higher sensitivity and a figure of merit, thus in the refractive index, sensing aspect is deeply concerned [ 6 , 7 ]. In 2010, Boris et al [ 8 ] reviewed the Fano resonance in plasmonic nanostructures, metal photonic crystals, and metamaterials, indicating that Fano resonance can be applied to label-free detection [ 9 ], filter [ 10 , 11 ], sensor [ 12 , 13 ], slow light device [ 14 , 15 ], optical switch [ 16 ], etc. Studies have shown that surface plasmon polaritons (SPP) are the electromagnetic wave produced by the interaction between free electrons and lightwave on the metal surface.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different plasmonic structures, SPPs-based MIM waveguide [27] structures at the subwavelength scale have aroused great interest due to their good properties of light confinement [28,29], the wide range of available frequencies, the absence of bending losses, and the ease of manufacturing. Accordingly, it is considered as an important and promising component in integrated optical circuits, and a promising candidate for integrated plasmonic biosensing devices [25,26,[29][30][31][32]. Zhang et al [30] proposed a plasmonic refractive index (RI) sensor based on MIM waveguide, coupled with a concentric double ring resonator (CDRR).…”
Section: Introductionmentioning
confidence: 99%